2022
DOI: 10.3390/ani12050635
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sophorolipid on Growth Performance, Organ Characteristics, Lipid Digestion Markers, and Gut Functionality and Integrity in Broiler Chickens

Abstract: Dietary fat and oil could aid in reaching the high-energy requirements of fast-growing birds; however, these inclusions could lead to nutrient waste. This is because young birds have limited lipid digestion due to the low secretion of lipase and bile salt. Sophorolipid (SPL), a glycolipid emulsifier with lower toxicity and higher biodegradability, can upregulate fat utilization by increasing digestibility. Accordingly, a five-week-long experiment was conducted with 720 one-day-old chicks (Ross 308) to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Shoaib et al (2022) reported that use of bile acids had improved weight gain, FCR and protein efficiency ratio than lysolecithin and lysophospholipid. Kwak et al (2022) used three levels (0.0005, 0.001 and 0.0015%) of Sophorolipid, a glycolipid emulsifier and observed that body weight was higher in grower phase with addition of 0.001% Sophorolipid in broiler diet. Shoaib et al (2021a) showed that use of bile acid at 0.05% in broilers diet had higher weight gain 2042 vs 1899g) and better FCR (1.58 vs 1.66).…”
Section: Effect Of Bile Acid On Growth Performance In Broilersmentioning
confidence: 99%
“…Shoaib et al (2022) reported that use of bile acids had improved weight gain, FCR and protein efficiency ratio than lysolecithin and lysophospholipid. Kwak et al (2022) used three levels (0.0005, 0.001 and 0.0015%) of Sophorolipid, a glycolipid emulsifier and observed that body weight was higher in grower phase with addition of 0.001% Sophorolipid in broiler diet. Shoaib et al (2021a) showed that use of bile acid at 0.05% in broilers diet had higher weight gain 2042 vs 1899g) and better FCR (1.58 vs 1.66).…”
Section: Effect Of Bile Acid On Growth Performance In Broilersmentioning
confidence: 99%
“…Recently, SPL has attracted much attention with its lower toxicity and more biodegradability compared to diverse biological detergents in various industrial fields including hygiene, medicine, and pharmacological fields [15]. SPL also could act as an antimicrobial agent, an immune modulator, a depigment agent, a wound healing accelerator, and a skin fibroblast stimulator [16][17][18]. Therefore, we conducted an experiment with SPL and zinc bacitracin to validate the possibility of SPL as a valuable replacement for AGP in livestock industry.…”
Section: Introductionmentioning
confidence: 99%